Computer-Automated Tinnitus Assessment: Noise-Band Matching, Maskability, and Residual Inhibition. - Henry, James A.; Roberts, Larry E.; Ellingson, Roger M.; Thielman, Emily J. (Journal of the American Academy of Audiology, 2013)
Background: Psychoacoustic measures of tinnitus typically include loudness and pitch match, minimum masking level (MML), and residual inhibition (Rl). We previously developed and documented a computer- automated tinnitus evaluation system (TES) capable of subject-guided loudness and pitch matching. The TES was further developed to conduct computer-aided, subject-guided testing for noise-band matching (NBM), MML, and Rl. Purpose: The purpose of the present study was to document the capability of the upgraded TES to obtain measures of NBM, MML, and Rl, and to determine the test-retest reliability of the responses obtained. Research Design: Three subject-guided, computer-automated testing protocols were developed to conduct NBM. For MML and Rl testing, a 2-12 kHz band of noise was used. All testing was repeated during a second session. Study Sample: Subjects meeting study criteria were selected from those who had previously been tested for loudness and pitch matching in our laboratory. A total of 21 subjects completed testing, including seven females and 14 males. Results: The upgraded TES was found to be fairly time efficient. Subjects were generally reliable, both within and between sessions, with respect to the type of stimulus they chose as the best match to their tinnitus. Matching to bandwidth was more variable between measurements, with greater consistency seen for subjects reporting tonal tinnitus or wide-band noisy tinnitus than intermediate types. Between-session repeated MMLs were within 10 dB of each other for all but three of the subjects. Subjects who experienced Rl during Session 1 tended to be those who experienced it during Session 2. Conclusions: This study may represent the first time that NBM, MML, and Rl audiometric testing results have been obtained entirely through a self-contained, computer-automated system designed specifically for use in the clinic. Future plans include refinements to achieve greater testing efficiency.